Penentuan Laju Korosi dan Remaining Service Life (RSL) Pipa Carbon Steel API 5L Grade B - Elton Mendy Simon; Firmanullah Fadlil; Ainul Alim Rahman (Universitas Pendidikan Muhammadiyah Sorong, 2025)
Corrosion is one of the main causes of material degradation in piping systems, which has a direct impact on safety and operational efficiency. The corrosion process, influenced by the environment, material type, and operational conditions, leads to the thinning of pipe walls over time. Therefore, evaluation of the corrosion rate is crucial in determining the remaining service life of pipes, allowing for mitigation measures to be planned before system failure occurs. This study aims to analyze the corrosion rate using a quantitative approach based on inspection data and to predict the remaining service life using a time-based degradation method. The pipe material examined in this study is API 5L Grade B with a maximum carbon content of 0.30%. The types of corrosion occurring in the internal piping of natural gas are erosion corrosion and crevice corrosion. The reduction of pipe thickness by 0.43 mm is caused by the natural gas content from the gas flow activities that contain hydrocarbon and non-hydrocarbon compounds. The corrosion rate of 0.165 mm/year results in a remaining service life of the pipe being 45 years. This corrosion rate shows a relatively good resistance to corrosion. The results of this study are expected to provide technical recommendations for the sustainable management of pipeline assets.